Investigating cognition in midlife - Novotný, Jan S; Gonzalez-Rivas, Juan P; Medina-Inojosa, Jose R; Lopez-Jimenez, Francisco; Geda, Yonas E; Stokin, Gorazd B (Alzheimer's & dementia (New York, N. Y.), 2021)
We here posit that measurements of midlife cognition can be instructive in understanding cognitive disorders. Even though molecular events signal possible onset of cognitive disorders decades prior to their clinical diagnoses, cognition and its possible early changes in midlife remain poorly understood. We characterize midlife cognition in a cognitively healthy population-based sample using the Cogstate Brief Battery and test for associations with cardiovascular, adiposity-related, lifestyle-associated, and psychosocial variables. Learning and working memory showed significant variability and vulnerability to psychosocial influences in midlife. Furthermore, midlife aging significantly and progressively increased prevalence of suboptimal cognitive performance. Our findings suggest that physiological changes in cognition, measured with simple tests suitable for use in everyday clinical setting, may signal already in midlife the first clinical manifestations of the presymptomatic biologically defined cognitive disorders. This pilot study calls for longitudinal studies investigating midlife cognition to identify clinical correlates of biologically defined cognitive disorders.
Keywords: quality of life; suboptimal cognition; cognitive performance; cognitive disorders; psychosocial variables; midlife cognition